2021
DOI: 10.1177/03915603211001175
|View full text |Cite
|
Sign up to set email alerts
|

Effects of severe hydronephrosis on the outcomes of percutaneous nephrolithotomy with one-shot dilation method

Abstract: Objective: To investigate the effect of the presence of severe hydronephrosis on percutaneous nephrolithotomy (PNL) outcome in patients who underwent PNL operation with one-shot dilatation technique. Materials and methods: Medical data of 989 patients underwent PNL operation in our clinic between 2012 and 2018 were retrospectively reviewed. We included 373 of the patients underwent PNL operation due to renal pelvic stone, who were older than 18 years of age, who did not have any urinary tract abnormality, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The edematous renal parenchyma can reduce the number of PCNL puncture trials due to the wider calyceal mouth and the more evident distribution of the contrast material. This could result in decreased punctural damage and lower operative duration,[ 24 ] lowering the rate of AKI occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The edematous renal parenchyma can reduce the number of PCNL puncture trials due to the wider calyceal mouth and the more evident distribution of the contrast material. This could result in decreased punctural damage and lower operative duration,[ 24 ] lowering the rate of AKI occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Micoogullari et al reported that the operation duration was shorter in the hydronephrosis group as compared to the cohort without hydronephrosis (although this difference was not statistically significant). Due to the wider caliceal mouth to be accessed and more evident distribution of opaque material in the pelvis, they mentioned that the presence of hydronephrosis may facilitate calyx access by reducing the attempts of renal puncture trials and thusly decreased the operative time [14]. Karatag et al compared the results of MPCNL with and without hydronephrosis.…”
Section: Discussionmentioning
confidence: 99%